Drug prevention in the school community - Martínez, Víctor; Covarrubias, Germán (Revista de Psicología, 1999)
The contents of this article are related with mental health promotion and drug prevention in scholar system. Educational units are conceptualised as school communities and the proposed model is formed by 4 conceptual indicators related with their capacity of contextual insertion, their sustaining rules that establish the frame (genostructure) of promotion and preventieve action, their settled capacities to produce promotional and preventive activities (fenoestructure) and the flow of concrete production of promotional an preventive activities (fenoprodutions). Based on the these indicators and index of preventive capacity of the school community is which allows to evaluate design interventions, strategies and public policies on this matter.